Effect of Evodiamine on Inducing Apoptosis of Human Gastric Cancer Cell Line SGC-7901 in Vitro - LIU Shao-ping (Journal of International Translational Medicine, 2014)
Objective: To explore the proliferation inhibition and apoptosis-inducing effect of evodiamine in human gastric cancer SGC-7901 cells. Methods: After 48 or 24 h exposure to different concentrations of evodiamine, cell proliferation was analyzed using tetrazolium blue (MTT) assay while apoptosis and cell-cycle phase distribution using flow cytometry. Results: In 0.01～30.00 μg/mL range of concentrations, evodiamine inhibited the proliferation of SGC-7901 cells in dose-dependent manner, and the overall mean IC50 was (3.79±0.16) μg/mL; the apoptosis rate was increased from 3.4% to 7.0%, 13.8% and 36.3% at concentrations of 0, 0.5, 1.5 and 30 μg/mL of evodiamine, respectively; the percentage of cells accumulated in G2/M phase was increased from 17.26% to 98.92% in the cells treated with evodiamine for 24 h in 0.01～30.00 μg/mL range of concentrations. Conclusion: Evodiamine can inhibit the proliferation, induce apoptosis in human gastric cancer cell line SGC-7901 in vitro and arrest the cell cycle at the G2/M phase.